Influenza vaccination for HIV-positive people: Systematic review and network meta-analysis. Issue 28 (27th June 2018) - Zhang, Wei; Sun, Huiying; Atiquzzaman, Mohammad; Sou, Julie; Anis, Aslam H.; Cooper, Curtis
Highlights: Thirteen RCTs were included in this systematic review and network meta-analysis. Eleven influenza vaccine strategies among HIV patients were compared. Adjuvant 7.5 μg booster and 60 μg single vaccines result in better patient outcomes. Abstract: Background: People with Human Immunodeficiency Virus (HIV) are highly susceptible to influenza-related morbidity and mortality. In order to assess comparative efficacy of influenza vaccine strategies among HIV-positive people, we performed a systematic review and Bayesian network meta-analysis (NMA). Methods: In this systematic review, we searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and CINAHL between 1946 and July 2015 for randomized controlled trials (RCTs) on influenza vaccines for HIV-positive adults reporting seroconversion or seroprotection outcomes. The NMAs were conducted within a Bayesian framework and logistic models were used for comparing the effect of the vaccine strategies on the two outcomes. Results: A total of 1957 publications were identified, 143 were selected for full review, and 13 RCTs were included in our final analysis. Fourteen separate NMAs were conducted by outcomes, vaccine strain, and different outcome measurement timepoints. For example, compared with the 15 μg single vaccine strategy, the odds ratio was the highest for the adjuvant 7.5 μg booster strategy (2.99 [95% credible interval 1.18–7.66]) when comparing seroconversion for H1N1 at 14–41 days after the last dose of vaccination and for the 60 μg single strategy (2.33 [1.31–4.18]) when comparing seroconversion for strain B. Conclusions: The adjuvant 7.5 μg booster and 60 μg single vaccine strategies provided better seroconversion and seroprotection outcomes. These findings have important implications for national and international guidelines for influenza vaccination for HIV-positive people and future research.